The Effect of Weighted Vests and Stability Balls With and Without Psychostimulant Medication on Classroom Outcomes for Children With ADHD - Macphee, Fiona L.; Merrill, Brittany M.; Altszuler, Amy R.; Ramos, Marcela C.; Gnagy, Elizabeth M.; Greiner, Andrew R.; Coxe, Stefany; Raiker, Joseph S.; Coles, Erika; Burger, Lisa; Pelham, William E. (School psychology review, 2019)
Current evidence-based, school-based interventions for children with attention deficit hyperactivity disorder (ADHD) include academic intervention, behavioral classroom management, and psychopharmacological intervention. However, some approaches that are commonly used have not been studied in controlled evaluations. The current study is the first rigorous evaluation of the effect of occupational therapy (OT) weighted vests and stability balls on classroom behavior and academic productivity in elementary-age children with ADHD (N = 64). The effect of psychostimulant medication and its combination with each of the OT interventions on classroom outcomes was also examined. The study consisted of a 2 (medication: methylphenidate, placebo) × 3 (OT intervention: stability ball, weighted vest, control) within-subjects design and was conducted over a 6-week period in a weekday, 60-min summer classroom. OT intervention was randomized daily within a medication crossover design. Overall, results indicated that medication but not weighted vest nor stability ball interventions resulted in improvement in two key areas of functioning in school settings: following classroom rules and academic productivity.